Transcriptional pathways of terminal differentiation in high- and low-density blood granulocytes in sepsis - Günther, Tobias; Coulibaly, Anna; Velásquez, Sonia Y.; Schulte, Jutta; Fuderer, Tanja; Sturm, Timo; Hahn, Bianka; Thiel, Manfred; Lindner, Holger A. (Journal of Inflammation, 2024)
Trauma and infection induce emergency granulopoiesis. Counts of immature granulocytes and transcriptional pathways of terminal granulocytic differentiation in blood are elevated in sepsis but correlate with disease severity. This limits their performance as sepsis biomarkers in critically ill patients. We hypothesized that activation of these pathways in sepsis is attributable to immature low-density (LD) rather than mature high-density (HD) granulocytes.